2014
DOI: 10.1002/ece3.1071
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paternity is a shared reproductive strategy in the live‐bearing surfperches (Embiotocidae) that may be associated with female fitness

Abstract: According to Bateman's principle, female fecundity is limited relative to males, setting the expectation that males should be promiscuous, while females should be choosy and select fewer mates. However, several surfperches (Embiotocidae) exhibit multiple paternity within broods indicating that females mate with multiple males throughout the mating season. Previous studies found no correlation between mating success and reproductive success (i.e., a Bateman gradient). However, by including samples from a broade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…This is due to mate choice 333 often being constrained by time, mobility, predation pressure and multiple males fighting over a single 334 female (commonly observed in green turtles). Thus the costs of comparing several potential mates can 335 be considerably high (Klemme, Eccard & Ylönen, 2006;LaBrecque et al, 2014). We find it more 336 likely that sea turtle female under breeding conditions might mate with the first male they encounter 337 and they will probably mate again if another male appears and so on.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…This is due to mate choice 333 often being constrained by time, mobility, predation pressure and multiple males fighting over a single 334 female (commonly observed in green turtles). Thus the costs of comparing several potential mates can 335 be considerably high (Klemme, Eccard & Ylönen, 2006;LaBrecque et al, 2014). We find it more 336 likely that sea turtle female under breeding conditions might mate with the first male they encounter 337 and they will probably mate again if another male appears and so on.…”
mentioning
confidence: 86%
“…While some 41 authors have argued that its prevalence is intriguing, due to the energetic fitness costs that such 42 behaviour incurs (Lee & Hays, 2004;Bilde et al, 2009), others have demonstrated how females may 43 gain indirect genetic benefits to offset the cost by mating with multiple males (Byrne & Roberts, 2000; 44 LaBrecque et al, 2014). For example, polyandry may provide genetic benefits by improving the 45 chance that females will acquire "good" genes or by enhancing the genetic diversity of their progeny 46 (Yasui, 1997 (Packer et al, 1991;Craighead et al, 1995;Keane, Dittus & Melnick, 1997;FitzSimmons, 1998; Uller 51 & Olsson, 2008) and enabling investigation into the genetic consequences of multiple matings.…”
Section: Alfaro-núñezmentioning
confidence: 99%
“…Previous studies have demonstrated that the frequency of MP varies both between (Moore & Ball, 2002;Hoekert et al, 2002;Crim et al, 2002;Theissinger et al, 2008;Noble et al, 2013), and within species (Galbraith, 1993;FitzSimmons, 1998;Ireland et al, 2003;Jensen et al, 2006;LaBrecque et al, 2014). For green turtles, evidence of MP has been reported in several studies, but the proportion of clutches with MP varies among populations.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors have argued that its prevalence is intriguing, due to the energetic fitness costs that such behaviour incurs (Lee & Hays, 2004;Bilde et al, 2009), others have demonstrated how females may gain indirect genetic benefits to offset the cost by mating with multiple males (Byrne & Roberts, 2000;LaBrecque et al, 2014). For example, polyandry may provide genetic benefits by improving the chance that females will acquire "good" genes or by enhancing the genetic diversity of their progeny (Yasui, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This is the case in many species of insects, gastropods, fish, amphibian, birds and reptiles (FitzSimmons, 1998;Garcia-Vazquez, 2001;Jones & Clark, 2003;Garcıá-González & Simmons, 2005;Chandler & Zamudio, 2008;Beese et al, 2008;Noble, Keogh & Whiting, 2013;LaBrecque et al, 2014); or in progeny from the same brood in mammals (Clapham & Palsbøll, 1997;Shurtliff, Pearse & Rogers, 2005). Thus, sperm competition may be an important factor in the evolution of reproduction of many organisms, although the precise mechanism that determines sperm success is not fully understood (Jones & Clark, 2003).…”
Section: Introductionmentioning
confidence: 99%